Employee Performance in the Dynamics of Transformational Leadership and Organizational Culture Through the Role of the Work Environment at Bank Muamalat Regional East Java - Mochammad Khoiruddin; Mardani , Ronny Malavia; Basalamah , Muhammad Ridwan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of transformational leadership and organizational culture on employee performance, with the work environment as a mediating variable at Bank Muamalat Regional East Java. This study uses a quantitative approach with a survey method and simple random sampling technique. The sample consisted of 100 respondents from five main branches, and data were collected using a Likert scale questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) with the AMOS program. Validity was tested using Confirmatory Factor Analysis (CFA), while reliability was measured through construct reliability and variance extracted with cutoff values of >0.70 and >0.50. The research model was deemed valid based on Goodness-of-Fit values such as CMIN/DF, GFI, TLI, RMSEA, and CFI, which were within acceptable criteria. The results indicate that transformational leadership and organizational culture have a significant positive influence on the work environment, while the work environment does not significantly influence employee performance. The work environment mediates the relationship between transformational leadership and employee performance, but does not mediate the relationship between organizational culture and employee performance. These findings confirm that in the context of Islamic banking, particularly at Bank Muamalat, employee performance is more influenced by transformational leadership and organizational culture than by the work environment alone. Therefore, human resource management strategies need to strengthen the integration of values, promote strong culture-based leadership, and create a more conducive work environment to enhance employee performance productivity